Peningkatan Prestasi Belajar Tentang Ciri-Ciri Khusus Hewan Melalui Model Pembelajaran Make A Match Menggunakan Bidak Catur di Kelas VI SDN Bendo 2 Kota Blitar - Maidi (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Abstract. Science learning at SDN Bendo 2 Blitar City shows results that do not meet the specified KKM. This is due to the lack of teacher creativity in carrying out learning. From the initial data on student scores after the evaluation was carried out, out of 38 students only 19 students or 50% had not achieved mastery of the material according to the KKM 70%. This study aims to describe learning achievement about the special characteristics of animals through a cooperative learning model of make a match type using chess pieces in class VI SDN Bendo 2 Blitar City. The research method uses a qualitative descriptive approach, while the CAR design is designed in two cycles, including planning, implementation, observation, and reflection. The research uses the Make a Match learning model using chess pieces, which is a teaching and learning method to find partners where students look for partners while learning about a concept or topic in a pleasant atmosphere. The number of students in one group should not be too large, consisting of 2 or more people.